2018
DOI: 10.1074/jbc.tm118.003343
|View full text |Cite
|
Sign up to set email alerts
|

Cancer pharmacoprevention: Targeting polyamine metabolism to manage risk factors for colon cancer

Abstract: Edited by Eric R. Fearon Cancer is a set of diseases characterized by uncontrolled cell growth. In certain cancers of the gastrointestinal tract, the adenomatous polyposis coli (APC) tumor suppressor gene is altered in either germline or somatic cells and causes formation of risk factors, such as benign colonic or intestinal neoplasia, which can progress to invasive cancer. APC is a key component of the WNT pathway, contributing to normal GI tract development, and APC alteration results in dysregulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 96 publications
1
66
0
1
Order By: Relevance
“…ODC1 overexpression may increase susceptibility to neoplastic transformation as polyamines are involved in epigenetic regulation of gene expression by interacting with histone acetyltransferases, deacetylases, and demethylase and thus affecting chromatin state and global transcription [67]. Targeting ODC1 is currently being tested as a chemoprevention strategy in CRC, which, however, is associated with adenoma-carcinoma transformation [13][14][15] and not inflammation-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ODC1 overexpression may increase susceptibility to neoplastic transformation as polyamines are involved in epigenetic regulation of gene expression by interacting with histone acetyltransferases, deacetylases, and demethylase and thus affecting chromatin state and global transcription [67]. Targeting ODC1 is currently being tested as a chemoprevention strategy in CRC, which, however, is associated with adenoma-carcinoma transformation [13][14][15] and not inflammation-induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in modulating the L-arginine/NO pathway as a chemopreventive strategy in CRC. Combination chemoprevention with ODC1 inhibitors has shown very promising results [13][14][15]. However, targeting ODC1 in IBD is controversial as polyamines are necessary for intestinal healing and gut health in general [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed an increase in the polyamines N 1 -acetylspermidine and N 1 ,N 12 -diacetylspermine. Polyamines are important mediators in colon carcinogenesis, and polyamine metabolism has been a target of preclinical and clinical chemoprevention studies going back decades 50,51 . Interestingly, Johnson et al observed increased levels of polyamines in patient-derived colorectal tumors that were biofilm-positive (in comparison to biofilm-negative tumors), and hypothesized that these metabolites were being contributed by the biofilm community 42 .…”
Section: Discussionmentioning
confidence: 99%
“…α-(Difluoromethyl)ornithine (DFMO) was synthesized in 1978 [13], and is the best-known and most widely used of the ODC inhibitors, serving for many years as the "gold standard inhibitor" of polyamine research [8,12]. DFMO is used as a drug to cure African sleeping sickness [14] and has also advanced in clinical trials with promising results as a cancer chemopreventive agent among populations with an elevated risk for specific epithelial cancers [15]. In addition, DFMO has fungicidal activity; this was demonstrated for the first time when it conferred protection on bean plants against infection by uredospores of the bean rust fungus Uromyces phaseoli Linnaeus in greenhouse experiments [16].…”
Section: Introductionmentioning
confidence: 99%